Insilico Approach on Selective Bioactive Compounds Identified From Annona Muricata Barkagainsthuman Estrogen Receptor Alpha (Pdb Id: 3ert) - S. Sudhashini; P. Amudha; T. Meera; G.Abirami; R.Priya; R. Satheesh Kumar (International Journal of Medical Toxicology and Legal Medicine, 2024)
The bark of Annona muricatahas been widely studied for its medicinal properties since the traditional use of the plant for its therapeutic purposes. In our study, we have performed GC-MS analysis of Annona muricata barkto identify the bioactive compounds that contribute to its pharmacological properties. The analysis revealed the presence of 25 compounds of which 1,2-Propadiene,1-(methylthio)-, 9,12-Octadecadienoic acid,Propanedioic acid Hexadecanoic acid and Trans-beta-ionone-5,6-epoxyde were most predominantly present. Molecular docking studies were performed to evaluate the binding affinity of these compounds with the human estrogen receptor alpha, which plays a vital role in hormone-dependent cancer therapy.Doxorubicin, a standard anticancer drug was used to evaluate the efficacy of these bioactive compounds identified by the GC-MS analysis. 9,12-Octadecadienoic acidwas found to exhibit the highest binding affinity of -6.00kcal/mol when compared to the standard drug. This study underscores the therapeutic potential of Annona muricatabark extract highlighting the need for further bioactivity assays and clinical investigations to validate the efficacy and the safety of the natural compound from the plant.